2019
DOI: 10.1002/ncp.10273
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Management in Patients With Chronic Gastrointestinal Motility Disorders: A Systematic Literature Review

Abstract: Background The aim of this study was to systematically review effects of nutrition interventions on outcomes in patients with chronic gastrointestinal (GI) motility disorders. There is currently a lack of evidence‐based guidelines for nutrition management in this group, likely a result of the rarity of the conditions. Methods A systematic review of all study types to evaluate current evidence‐based nutrition interventions was performed using Medline, Embase, and CINAHL databases. Two independent reviewers part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
11
0
1
Order By: Relevance
“…After the pioneering randomized, controlled trial by Olausson et al (55) demonstrated efficacy of small particle diet compared with normal diet for relief of symptoms, improving GE and enhancing glycemic control (56) in patients with diabetes, a systematic review (57) of all study types evaluated current evidence-based nutrition interventions involving a total of 15 studies and of 524 subjects, using a stepwise process, progressing from oral nutrition to jejunal nutrition and lastly to parenteral nutrition. Small particle, low-fat diets were significantly better tolerated than the converse, with jejunal nutrition before consuming oral food significantly improving oral intake and motility.…”
Section: Management Of Gpmentioning
confidence: 99%
“…After the pioneering randomized, controlled trial by Olausson et al (55) demonstrated efficacy of small particle diet compared with normal diet for relief of symptoms, improving GE and enhancing glycemic control (56) in patients with diabetes, a systematic review (57) of all study types evaluated current evidence-based nutrition interventions involving a total of 15 studies and of 524 subjects, using a stepwise process, progressing from oral nutrition to jejunal nutrition and lastly to parenteral nutrition. Small particle, low-fat diets were significantly better tolerated than the converse, with jejunal nutrition before consuming oral food significantly improving oral intake and motility.…”
Section: Management Of Gpmentioning
confidence: 99%
“…Information regarding radiology, manometry, and pathology for diagnosing GID and its variant is not part of the registry. However, the participating programs are academic centers, where it is expected that diagnoses and management of GID follow recommended pathways and guidelines 6,7,15 . We did not look into intravenous fluid supplement types or volume, which may have a prognostic factor in patients with chronic intestinal failure 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It encompasses enteric dysmotility, chronic intestinal pseudo‐obstruction (CIPO), GI neuromuscular disease, and other secondary causes such as diabetes, scleroderma, and autonomic failure 6 . Infrequently, the affected patients with severe GID are unable to tolerate oral or enteral nutrition, and thus, the use of HPN for life is inevitable 7 . Complications and survival of GID patients may be different depending on the underlying disease.…”
Section: Introductionmentioning
confidence: 99%
“…These included use of EN for GI and non‐GI disorders as well as in a range of clinical scenarios, including patients with malignancy, especially head and neck cancer, 20,21 as well as neurodegenerative, 22 hepatic‐biliary/pancreatic, 23,24 or renal 25 disorders. EN can also be beneficial in challenging cases such as intestinal failure involving severe GI dysmotility 26 or in special groups, such as in patients who underwent bariatric surgery 27 . Unfortunately, despite these benefits, long‐term EN can be a challenging and overwhelming experience for patients and caregivers alike 28 .…”
Section: Introductionmentioning
confidence: 99%